Mast cells are critically involved in serum-mediated vascular leakage in chronic urticaria beyond high-affinity IgE receptor stimulation. - Bossi, F; Frossi, B; Radillo, O; Cugno, M; Tedeschi, A; Riboldi, P; Asero, R; Tedesco, F; Pucillo, C (Allergy, 2011)
BACKGROUND: Chronic urticaria (CU) is one of the most common skin disorders whose pathogenic mechanisms are not fully clarified. Autoimmune aetiology can be ascribed to 45% of patients with CU, and basophil histamine release is positive in 40% of cases. Our aim was to use a novel approach to evaluate the serum permeabilizing effect to identify the mediators of endothelial cell (EC) leakage and to define the role of mast cells (MCs) in the process. METHODS: Permeabilizing activity of sera from 19 patients with CU and 11 healthy blood donors was evaluated by measuring serum-induced degranulation of two MC lines, expressing (LAD2) or lacking (HMC-1) the IgE receptor. Mast cell supernatant (SN) was then incubated with an EC monolayer, and endothelial permeability was evaluated by Fluorescein isothiocyanate-bovine serum albumin leakage in a transwell system. RESULTS: All 19 patient sera failed to induce direct EC leakage, but 15/19 and 17/19 promoted degranulation of HMC-1 and LAD2, respectively. Interestingly, 85% of autologous serum skin test-negative sera were able to cause MC degranulation. Also, 17/19 SNs from HMC-1 and all SNs from LAD2 incubated with CU sera increased endothelial permeability. Endothelial cell leakage remained unchanged after Ig depletion and was prevented by antihistamine, platelet-activating factor or leukotriene antagonist. CONCLUSIONS: Our study shows that CU sera are able to degranulate MCs through an IgE- and IgG-independent mechanism. The nature of histamine-releasing factors involved is still unclear, but our finding opens new ways to the understanding of the pathogenesis of CU, particularly in patients not showing circulating autoantibodies to FcεRI or IgE.
Keywords: Adult; Aged; Capillary Permeability; Chronic Disease; Endothelial Cells; Female; Histamine Release; Humans; Male; Mast Cells; Middle Aged; Receptors, IgE; Serum; Urticaria; Young Adult